Education and training of telemental health providers: a systematic review - Jiang, Qiaoling; Deng, Yongjia; Perle, Jonathan; Zheng, Wanhong; Chandran, Dilip; Chen, Jingru; Liu, Feiyue (Frontiers in Public Health, 2024)
Objective To conduct a systematic literature review of education and training (E&T) programs for telemental health (TMH) providers in the past 10 years to qualitatively clarify field offerings and methodologies, as well as identify areas for future growth. Methods We searched five major electronic databases: PubMed, PsycINFO, Scopus, CINAHL, and Web of Science for original publications on TMH E&T from January 2013 to May 2023. We extracted information from each publication and summarized key features of training programs including setting, target group, study aims, training modality, methods of assessing quality, and outcomes. Results A total of 20 articles were selected for the final review. Articles meeting inclusionary criteria were predominantly comprised of case studies and commentaries, focused on a TMH service/practice for a specific region/population, and were performed after 2020. All of the selected studies demonstrated a significant increase in the measured knowledge, skills, and abilities of the participants after TMH training. Nevertheless, there remains a lack of standardization of training methodologies, limited sample sizes and demographics, variability in study methodologies, and inconsistency of competency targets across studies. Conclusion This systematic review highlighted the diversity of methods for TMH E&T. Future research on this topic could include more varied and larger-scale studies to further validate and extend current findings, as well as explore potential long-term effects of TMH training programs on both provider attitudes and patient outcomes.